Deconstructing the Properties of Solar Super Active Region 13664 in the Context of the Historic Geomagnetic Storm of 2024 May 10–11 - Priyansh Jaswal; Suvadip Sinha; Dibyendu Nandy (The Astrophysical Journal)
Active regions (ARs) are sites of strong magnetic fields on the solar surface whose size can be several times that of Earth. They spawn dynamic activity, sometimes resulting in severe space weather. Some ARs characterized by extraordinary magnetic properties and exhibiting extreme activity are termed as super active regions (SARs). Recently, solar AR 13664 produced 23 X-class flares and unleashed multiple coronal mass ejections, which triggered a severe geomagnetic storm during 2024 May 10–11—the strongest storm on record since 2003. Here, we put AR 13664 in historical context over the cumulative period of 1874 May–2024 June. We find that AR 13664 stands at the 99.95th percentile in the distribution of area over 1874 May–2024 June and at the 99.10th percentile in terms of flux content among all ARs over the period 1996 April–2024 June. Our analysis indicates that five of its magnetic properties rank at the 100.00th percentile among all ARs observed during 2010 May–2024 June by the Solar Dynamic Observatory. A total of 16 magnetic properties of AR 13664 are ranked higher than the 99.00th percentile when compared to other ARs recorded in Space-weather Helioseismic Magnetic Imager Active Region Patch data series, which includes all well-established flare relevant parameters. Furthermore, we demonstrate that AR 13664 reached its most dynamic flare productive state following a rapid rate of rise of its flare-relevant parameters and that the X-class flares were more frequent near their peak values. Our analyses establish AR 13644 to be an SAR and provide a paradigm for investigating their flare-relevant physical characteristics.